Quality Assurance (QA) Dan Quality Control (QC) Pada Instrumen Radioterapi Pesawat LINAC - Bambang Haris Suharmono; Ika Yuni Anggraini; Hilmaniyya Hilmaniyya; Suryani Dyah Astuti (Universitas Airlangga, 2020)
Abstract LINAC is a radiotherapy instrument used to kill tumor and cancer cells in patients. To guarantee the quality of LINAC instruments, QA (Quality Assurance) is needed and to prove the quality assurance there is a need for QC (Quality Control). This is done also aims to examine and test data to determine standards and check the suitability of products to achieve maximum manufacturing operations or measures taken, namely to assess, maintain or improve the quality of treatment given. The role of medical physicists is very important because only medical physicists carry out the implementation of quality assurance of radiotherapy instruments. Keywords: Radiotherapy, Linear Accelerator, Quality Assurance, Quality Control AbstrakLINAC adalah instrumen radioterapi yang digunakan untuk mematikan sel tumor maupun kanker pada pasien. Untuk menjamin kualitas instrumen LINAC, maka diperlukan QA (Quality Assurance) dan untuk membuktikan adanya jaminan kualitas perlu QC (Quality Control). Hal ini dilakukan juga bertujuan untuk memeriksa dan menguji data untuk menentukan standar dan mengecek kesesuaian produk mencapai operasi manufaktur yang maksimum atau ukuran yang diambil yaitu untuk menilai, merawat atau memperbaiki kualitas perlakuan yang diberikan. Peran fisikawan medis sangat penting karena hanya fisikawan medis yang menjalankan pelaksanaan jaminan kualitas instrumen radioterapi. Kata kunci: Radioterapi, Linear Accelerator, Quality Assurance, Quality Control